Let’s Coerce All the Lawyers: Revocation of Attorney Security Clearances as a Jawbone - Tobin Raju (Washington University Journal of Law and Policy, 2026)
In an effort to manipulate and control lawyers’ representation of clients and causes at odds with the Trump administration, the Executive Branch has revoked attorneys’ security clearances. In early February 2025, President Trump instructed intelligence agencies to revoke the security clearances of any employees of law firm Covington & Burling LLP, the firm assisting former Special Counsel Jack Smith, who spearheaded criminal charges against then-former President Trump. This revocation set off a series of executive orders, memoranda, and intensive dealmaking between the Trump administration and cornered law firms across the country: continue to represent the enemies of the administration and risk losing critical information needed to represent their clients’ interests, or capitulate at the expense of those very clients. This campaign against lawyers is a prime example of ‘jawboning,’ where government officials coerce or intimidate private actors, here being lawyers and law firms, via indirect methods of speech suppression and a trump on legal advocacy that would not be legal if done directly. Jawboning stands as a threat to a very fundamental principle of American democracy: the freedom to provide and seek independent legal representation. The First Amendment has long-protected advocates in their representation of clients, namely utilizing the right of speech, petition, and association to do so. These fundamental protections have created the foundation to the civil rights system, the rule of law, and critically, government accountability. Despite jawboning’s antithetical nature to our democratic values, how can court systems analyze jawbone claims? This Essays seeks to answer that question by reviewing the Executive actions against lawyers and their chilling impact on speech protections. This Essay will analyze and evaluate the First Amendment foundations that safeguard legal advocacy and the right to counsel in the national security context. Finally, through a review of the security revocation of Mark Zaid and the Supreme Court’s analysis of jawboning in National Rifle Association v. Vullo, this Essay will make the case for a robust jawboning doctrine, one that is especially needed when First Amendment and democratic values are so undermined.
Keywords: #Jawboning; #SecurityClearance; #AttorneyIndependence; #FirstAmendmentRetaliation; #WhistleblowerProtection